Q waves are the strongest electrocardiographic variable associated with primary prophylactic implantable cardioverter-defibrillator benefit: a prospective multicentre study - Pelli, Ari; Junttila, M Juhani; Kenttä, Tuomas V; Schlögl, Simon; Zabel, Markus; Malik, Marek; Reichlin, Tobias; Willems, Rik; Vos, Marc A; Harden, Markus; Friede, Tim; Sticherling, Christian; et al. (Europace, 2022)
AIM: The association of standard 12-lead electrocardiogram (ECG) markers with benefits of the primary prophylactic implantable cardioverter-defibrillator (ICD) has not been determined in the contemporary era. We analysed traditional and novel ECG variables in a large prospective, controlled primary prophylactic ICD population to assess the predictive value of ECG in terms of ICD benefit. METHODS AND RESULTS: Electrocardiograms from 1477 ICD patients and 700 control patients (EU-CERT-ICD; non-randomized, controlled, prospective multicentre study; ClinicalTrials.gov Identifier: NCT02064192), who met ICD implantation criteria but did not receive the device, were analysed. The primary outcome was all-cause mortality. In ICD patients, the co-primary outcome of first appropriate shock was used. Mean follow-up time was 2.4 ± 1.1 years to death and 2.3 ± 1.2 years to the first appropriate shock. Pathological Q waves were associated with decreased mortality in ICD patients [hazard ratio (HR) 0.54, 95% confidence interval (CI) 0.35-0.84; P < 0.01] and patients with pathological Q waves had significantly more benefit from ICD (HR 0.44, 95% CI 0.21-0.93; P = 0.03). QTc interval increase taken as a continuous variable was associated with both mortality and appropriate shock incidence, but commonly used cut-off values, were not statistically significantly associated with either of the outcomes. CONCLUSION: Pathological Q waves were a strong ECG predictor of ICD benefit in primary prophylactic ICD patients. Excess mortality among Q wave patients seems to be due to arrhythmic death which can be prevented by ICD.
Keywords: Arrhythmias, Cardiac; Risk Factors; Death, Sudden, Cardiac; Electrocardiography; prospektivní studie; lidé; rizikové faktory; Humans; Primary Prevention; elektrokardiografie; Prospective Studies; primární prevence; Defibrillators, Implantable; srdeční arytmie; defibrilátory implantabilní; náhlá srdeční smrt